Mayorships with efficacious, efficient and effective public management previously planned during the political campaign (2010)
In Colombian towns, public management is led by the mayor, appointed by popular election. During the political campaign, candidates implement different strategies to show the citizens they deserve to be elected. Political campaigns in Colombia use money as a factor of competitiveness. The present paper, deriving from the civic observatory in Cartagena de Indias, proposes an instruction manual to become a mayor candidate. The aforementioned instruction manual might be extended to all positions of popular election stressing on substantial changes in the electoral process as an influential element in the future public management.